Internal corporate governance mechanisms and audit report lag: a study of Malaysian listed companies - Ummi Junaidda, Hashim (2012)
This study attempts to investigate the link between corporate governance mechanisms and audit report lag for companies listed on Bursa Malaysia from 2007 to 2009. The 288 companies listed on Bursa Malaysia have been randomly selected. The corporate governance mechanisms examined include the board of directors and audit committee. It shows that there are significant negative relationships between board diligence, audit committee independence and expertise. The higher the number of meetings being held indicates that the board is discharging their role towards the company. The results show that audit committee independence and audit committee expertise could assist in reducing audit report lag among companies in Malaysia. Its provide some evidence supporting the resource based theory, whereby characteristics of the audit committee, such as the resources and capabilities, could improve companies' performance as well as corporate reporting.However, it could not provide any evidence concerning the link between board independence, board expertise, CEO duality and audit committee diligence on audit report lag. This study provides comprehensive examination of ARL on Malaysian listed companies for three years period. It is consider the initial study to provide a thorough examination of the association between corporate governance characteristics and ARL.